1977
DOI: 10.1161/01.res.40.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sympathetic neurotransmission in canine blood vessels by adenosine and adenine nucleotides.

Abstract: SUMMARY Adenosine and the adenine nucleotides caused a greater relaxation of strips of canine saphenous vein and tibial artery when they had been contracted by nerve stimulation than by exogenous norepinephrine. An infusion of adenosine into the dogs' lateral saphenous vein, perfused at constant flow, caused a greater relaxation of this vein when constricted by electrical stimulation of the lumbar sympathetic chain than by exogenous norepinephrine. That this difference was due to inhibition by these compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(54 citation statements)
references
References 23 publications
12
41
1
Order By: Relevance
“…This is consistent with the evidence for an inhibition of transmitter release from both peripheral and central cholinergic and adrenergic neurones (Ginsborg & Hirst, 1972;Ribeiro & Walker, 1975;Sawynok & Jhamandas, 1976;Hedqvist & Fredholm, 1976;Vizi & Knoll, 1976;Clanachan et al, 1977;Enero & Saidman, 1977;Gustafsson et al, 1978;Paton et al, 1978). The ability of theophylline to prevent this effect also suggests that a receptor is involved similar to that which has been found to mediate effects of adenosine on transmitter release in other systems (Ginsborg & Hirst, 1972;Sawynok & Jhamandas, 1976;Verhaeghe et al, 1977;Su, 1978) as well as the effects of adenosine on adenylate cyclase (Sattin & Rall, 1970;Blume, Dalton & Sheppard, 1973;Sattin, Rall & Zanella, 1975) depression of neuronal firing (Phillis & Kostopoulos, 1975;Stone & Taylor, 1977;Taylor & Stone, 1978) and vascular tone (Wahl & Kuschinsky, 1976). Further the antagonism by theophylline and the greater potency of adenosine compared with ATP suggests that the receptor involved is that recently classified as PI by Burnstock (1978).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is consistent with the evidence for an inhibition of transmitter release from both peripheral and central cholinergic and adrenergic neurones (Ginsborg & Hirst, 1972;Ribeiro & Walker, 1975;Sawynok & Jhamandas, 1976;Hedqvist & Fredholm, 1976;Vizi & Knoll, 1976;Clanachan et al, 1977;Enero & Saidman, 1977;Gustafsson et al, 1978;Paton et al, 1978). The ability of theophylline to prevent this effect also suggests that a receptor is involved similar to that which has been found to mediate effects of adenosine on transmitter release in other systems (Ginsborg & Hirst, 1972;Sawynok & Jhamandas, 1976;Verhaeghe et al, 1977;Su, 1978) as well as the effects of adenosine on adenylate cyclase (Sattin & Rall, 1970;Blume, Dalton & Sheppard, 1973;Sattin, Rall & Zanella, 1975) depression of neuronal firing (Phillis & Kostopoulos, 1975;Stone & Taylor, 1977;Taylor & Stone, 1978) and vascular tone (Wahl & Kuschinsky, 1976). Further the antagonism by theophylline and the greater potency of adenosine compared with ATP suggests that the receptor involved is that recently classified as PI by Burnstock (1978).…”
Section: Discussionsupporting
confidence: 84%
“…This action has been studied at both cholinergic (Ginsborg & Hirst, 1972; Ribeiro & Walker, 1975;Sawynok & Jhamandas, 1976;Vizi & Knoll, 1976;Gustafsson, Hedqvist, Fredholm & Lundgren. 1978) and adrenergic (Hedqvist & Fredholm, 1976;Clanachan, Johns & Paton, 1977;Enero & Saidman, 1977;Verhaeghe, Vanhoutte & Shepherd, 1977;Su, 1978;Paton, Bar, Clanachan & Lauzon, 1978) terminals in the peripheral nervous system. It has recently been concluded that adenosine can also reduce acetylcholine release at the synapse between motor axon collaterals and Renshaw cells (Lekic, 1977), and noradrenaline release from terminals in the cerebral cortex in vivo (Taylor & Stone, 1980) and in vitro (Harms, Wardeh & Mulder, 1978 (Bowery & Brown, 1974 …”
Section: Introductionmentioning
confidence: 99%
“…Since the decreases in tension caused by adenosine and AMP were unaffected by the procedure, an explanation could be that, as is presumably the case for the prejunctional inhibitory effect of ATP (Verhaeghe, Vanhoutte & Shepherd, 1977; De Mey, Burnstock & Vanhoutte 1979), ATP (and ADP) must be degraded to adenosine (or AMP) by the endothelial cells in order to exert their inhibitory effect on the vascular smooth muscle cells of the media, but that the latter lack the enzymes necessary for this degradation. This interpretation is hard to reconcile with: (1) the findings that a concentration of theophylline which abolishes the relaxations caused by adenosine does not affect the inhibition evoked by ATP, and (2) the observation that ATP but not adenosine…”
Section: Potassiummentioning
confidence: 99%
“…P2-purinoceptors are described as being preferentially activated by ATP and adenosine 5'-diphosphate (ADP); these were initially divided into P2X and P2Y subgroups, based on potency orders of ATP analogues (Burnstock & Kennedy, been identified (Vials & Burnstock, 1993). Activation of Alpurinoceptors generally mediates prejunctional inhibition of neurotransmitter release (Verhaeghe et al, 1977).…”
Section: Introductionmentioning
confidence: 99%